Penanggulangan Tindak Pidana Korupsi Dana Bantuan Sosial Pada Saat Bencana Alam - Mulyadi, Mulyadi; Wijaya, Vivian; Sitorus, Marthin Erixon; Pakpahan, Kartina (Fakultas Syariah INSURI Ponorogo, 2023)
Corruption is a crime that harms state finances and the people's economy. On KPK website, cases of budget misuse data based on region, from 2004 to 2021 there are as many as 402 cases. So, extraordinary enforcement and extraordinary measures are needed. The research purpose is to analyze the regulation of corruption crimes committed during natural disasters, analyze the weaknesses of regulation corruption in social assistance funds, and analyze the prevention of corruption during natural disasters. This study uses statute approach with secondary legal literature research techniques and uses prescriptive analysis. The result of this journal is regulation of Corruption Crimes during natural disasters is regulated in Law Number 24 of 2007 about Disaster Control, Law Number 31 of 1999 about Eradication of Corruption Crimes, and PERPU Number 24 of 1960 about Investigation, Prosecution and Examination of Corruption Crimes. Provisions for the death penalty are regulated in Article 2 paragraph 2 Law Number 31 of 1999, namely in event that criminal act of corruption as referred to in paragraph (1) is committed under certain circumstances, the death penalty can be imposed, and prevention of corruption during a natural disaster can be carried out by penal and non-penal.